APPLICATION AND INNOVATION OF DIGITAL EXHIBITION DESIGN IN THE DISSEMINATION OF CHINESE INTANGIBLE CULTURAL HERITAGE - HE , QIYING; KOSENKO, D. (Art and Design, 2024)
Purpose. This paper explores the application and innovation of digital exhibition design in disseminating Chinese Intangible Cultural Heritage (ICH), with a focus on preserving aesthetic qualities such as color symbolism, spatial organization, and material authenticity. By prioritizing these aesthetic elements, the research demonstrates how digital technologies can enhance the visual and cultural fidelity of ICH, ensuring that traditional art forms are not only accessible but also artistically authentic in a digital context. Methodology. The study adopts an integrative approach, utilizing Virtual Reality (VR), Augmented Reality (AR), and 3D modeling to create digital exhibitions for three representative ICH projects: Shadow Puppetry, Woodblock New Year Prints, and Traditional Chinese Medicine. The research process emphasizes aesthetic design principles, covering conceptual development, digital adaptation, and visual enhancement, to maintain the cultural essence of ICH in digital formats. Results. The findings reveal that digital exhibitions can effectively preserve the aesthetic integrity of Chinese ICH by incorporating traditional elements like symmetry, color symbolism, and material authenticity into their design. The analysis highlights how these aesthetic elements enhance the cultural representation of ICH, demonstrating that digital technologies can function as artistic tools that convey cultural narratives faithfully, rather than solely focusing on interaction or accessibility. Scientific novelty. This study contributes a new perspective by emphasizing aesthetic preservation in digital exhibition design for ICH. It offers a detailed analysis of how digital technologies can replicate visual and material qualities, addressing existing gaps in research regarding the balance between cultural authenticity and digital innovation in the preservation of intangible heritage. Practical significance. The insights gained from this study are valuable for museum professionals, exhibition designers, and cultural heritage practitioners. By providing guidelines for integrating aesthetic elements into digital exhibition design, the study supports the creation of digital platforms that are not only interactive but also visually authentic, ensuring that ICH retains its cultural and artistic value in contemporary society.